Do high-stakes matter? : Evidence from a probation policy in higher education - Brox, Enzo [Verfasser]; Dörsam, Michael [Verfasser] (My University, 2025)
“Universities in many countries have introduced early requirements that students need to fulfill to be allowed to proceed. However, their effectiveness is disputed because of concerns that they harm graduation chances. We study the impact of a last-chance exam mechanism applying a quasi-experimental design. We exploit the discontinuity in treatment status around the promotion cutoff and show that exposure to a last-chance exam increases early dropout. Graduation chances are on average not affected. However, we find small negative effects on the graduation chances of female students. Further performance measures are largely unaffected.” (authors’ abstract; BIBB-Doku)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; P 2.1 Schulabgänger; 370; Hochschulzugang; Studienberechtigung; Zugangsvoraussetzung; Schulabschluss; Prüfung